2018
DOI: 10.1186/s12931-018-0835-7
|View full text |Cite
|
Sign up to set email alerts
|

Decreased microbiome diversity in the HIV small airway epithelium

Abstract: BackgroundPersons living with human immunodeficiency virus (PLWH) face an increased burden of chronic obstructive pulmonary disease (COPD). Repeated pulmonary infections, antibiotic exposures, and immunosuppression may contribute to an altered small airway epithelium (SAE) microbiome.MethodsSAE cells were collected from 28 PLWH and 48 HIV- controls through bronchoscopic cytologic brushings. DNA extracted from SAE cells was subjected to 16S rRNA amplification and sequencing. Comparisons of alpha and beta divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…Dysbiosis of the gut microbiome has been linked to multiple disease states, including in ammatory bowel disease and critical illness (5,6). Measures of diversity are possibly the most wellknown parameter describing a microbiome (7), however, the composition (or relative abundance of certain phyla or taxa), as well as the total microbial burden are also relevant characteristics (1,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Dysbiosis of the gut microbiome has been linked to multiple disease states, including in ammatory bowel disease and critical illness (5,6). Measures of diversity are possibly the most wellknown parameter describing a microbiome (7), however, the composition (or relative abundance of certain phyla or taxa), as well as the total microbial burden are also relevant characteristics (1,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…For example, recently published studies have suggested that lung disease in PWH could be related to factors such as a potential latent lung HIV reservoir, persistent viral protein production (e.g. Nef and Tat), oxidative stress, and alterations in the respiratory microbiome [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Feature selection was performed using the Boruta method to determine which bacterial contributors are important to the observed differences between groups 16 . Microbiome toolsets have incorporated Boruta as a feature selection method, 17 and it has previously been used to analyze human microbiota in several studies 18‐20 …”
Section: Methodsmentioning
confidence: 99%